Financial Indicator Analysis On Companies Inside The Watchboard List Of Indonesia Stock Exchange - Kurniawan , Jodhi; Muchlis, Muchlis; Simatupang, Batara Maju; Sparta, Sparta (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2024)
In June 2023, Indonesia Stock Exchange (IDX) announced the watchboard list, comprised of underperforming companies struggling to meet financial requirements. As of September 11 2024, this list includes 223 companies. This research studied the financial indicators that may influence whether a company will be put in IDX watchboard list, and attempted to generate a model to predict whether a company will be placed inside IDX watchboard list in the next two years. The sample data used are the financial indicators of companies on the IDX watchboard list on the year of 2022 and 2023. The sample data also includes companies outside the IDX watchboard list, random sampled so that the number of data of companies inside the IDX watchboard list is the same with the number of data of companies inside the IDX watchboard list. The finding suggests all these financial indicators have influence: WOTA (working capital divided by total asset), RETA (retained earnings divided by total asset), EBTTA (earnings before taxes divided by total asset), PBV (market value of equity divided by book value of equity) and STA (total sales divided by total asset). Investors may use the prediction models generated in this research in deciding whick stocks to buy. This research generated a MDA based prediction model and a logistic regression based prediction model that may predict whether a company will be place inside IDX watchboard list in the coming two years. The logistic regression based prediction model shows better results that the MDA based one.